Evolusi Dalam Kehidupan Sehari-Hari: Sudut Pandang Mahasiswa Terhadap Evolusi - Yasir Sidiq (Universitas Sebelas Maret, 2016)
Evolution is one of courses in Unversitas Muhammadiyah Surakarta. This research was aimed to indentify student ability to (1) understood the definition of evolution and (2) mentioned the examples of evolution phenomenon in their daily activities. Methode of this research was open examination for student by Contextual Teaching and Learning (CTL) methode and authentic evaluation. Students sugessted by many evolution concept from early publication then they examined to search evolution phenomenon from their daily. Student activities evaluated then generalized. The data obtained on odd semester of 2015/2016 academis year. They were analized by descriptive statistics. Samples of this research were 50 students from 3 groups. Results of this research were most of students (80%) of biology education V grade well known and known about evolution concepts and most of students (72%) mention cultural evolution.